PEMANFAATAN MEDIA SOSIAL SEBAGAI LITERASI MEMBACA DALAM MENINGKATKAN SEMANGAT BELAJAR PADA PANTI YATIM PELITA KAMIL - Wilsen (Jurnal Abdi Citra, 2024)
This community service activity aims to increase interest in reading at the Pelita Kamil orphanage through the use of social media. The method of implementing this community service uses assistance by implementing reading activities for 20minutes every day and writing down the reading results obtained from social media. The results of this community service activity can increase children's interest in reading with a satisfaction level of 80% from the indicator of usefulness for activity participants. The indicators of the success of this service also include the equipment used during the activity, the atmosphere and situation during the implementation of the activity, the time of implementation, media, reading materials, guidance from the resource person, reading literacy practices, the resource person's ability to adapt, and mastery of the material from theresource person.